Experimental Evaluation of Wound Healing Activity of Various Dosage Forms of Tridax Procumbens - Swati Ambulkar1 , Pranit Ambulkar2 , Manish P. Deshmukh3 , Ashish B. Budhrani (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Tridax procumbens Linn. (Tridax) is a common weed found all over India. It is commonlyknown as Peet Bhringraj, Jakhamjod and Kambarmodi etc. It is traditionally being used since centuries forwound healing and haemostasis and also for the treatment of diarrhea, dysentery, bronchial catarrh etc.Need of the Study: Tridax is traditionally being used in its crude form. Despite of the marked utility ofTridax in wound management, in Ayurvedic literature neither there is much description of Tridax nor itsdosage forms are mentioned. Exploring the various dosage formsObjective: Thus the study is designed to find out an effective Ayurvedic dosage form of Tridax that is moreeffective and on the same hand is holistic in approach as per principles of Ayurveda.Materials and Method: An animal experiment is conducted on Albino rats using excision wound model.Five dosage forms of Tridax were prepared such as Ash, Kalka, Oil, Ghana and Ethanolic extract and werecompared with control to evaluate rate of contraction and period of epithelialization.Results and Conclusion: The results were outstanding. Different dosage forms of Tridax exhibited excellentwound healing property. Few dosage forms exhibited typical behavior in different stages of wound healing.Hence Tridax can be seen as a potent drug to develop a good wound healing agent of future.